Biogenesis and Function of T Cell-Derived Exosomes - Ventimiglia, Leandro N.; Alonso, Miguel A. (Frontiers in Cell and Developmental Biology, 2016)
Exosomes are a particular type of extracellular vesicle, characterized by their endosomal origin as intraluminal vesicles present in large endosomes with a multivesicular structure. After these endosomes fuse with the plasma membrane, exosomes are secreted into the extracellular space. The ability of exosomes to carry and selectively deliver bioactive molecules (e.g., lipids, proteins and nucleic acids) confers on them the capacity to modulate the activity of receptor cells, even if these cells are located in distant tissues or organs. Since exosomal cargo depends on cell type, a detailed understanding of the mechanisms that regulate the biochemical composition of exosomes is fundamental to a comprehensive view of exosome function. Here, we review the latest advances concerning exosome function and biogenesis in T cells, with particular focus on the mechanism of protein sorting at multivesicular endosomes. Exosomes secreted by specific T-cell subsets can modulate the activity of immune cells, including other T-cell subsets. Ceramide, tetraspanins and MAL have been revealed to be important in exosome biogenesis by T cells. These molecules, therefore, constitute potential molecular targets for artificially modulating exosome production and, hence, the immune response for therapeutic purposes.